2005
DOI: 10.1001/archpsyc.62.3.247
|View full text |Cite
|
Sign up to set email alerts
|

The Lifetime Risk of Suicide in Schizophrenia

Abstract: This study estimates that 4.9% of schizophrenics will commit suicide during their lifetimes, usually near illness onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
477
3
32

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 892 publications
(535 citation statements)
references
References 71 publications
23
477
3
32
Order By: Relevance
“…This is in accordance with previous findings that suicide risk changes with time and suicide ideation occurs mostly early in the course of illness (Palmer et al, 2005;Nordentoft et al, 2004). Suicide ideators and attempters were mostly men with lower level of education and retired due to illness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with previous findings that suicide risk changes with time and suicide ideation occurs mostly early in the course of illness (Palmer et al, 2005;Nordentoft et al, 2004). Suicide ideators and attempters were mostly men with lower level of education and retired due to illness.…”
Section: Discussionsupporting
confidence: 93%
“…Today suicide is the leading cause of premature death in schizophrenia with approximately 5% completing suicide. (Inskip et al, 1998, Palmer et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the mechanisms underlying suicidal behaviour remain poorly understood, research has shown that it is likely determined by a complex interplay of biological, psychological, environmental and cultural factors (O'Connor et al, 2011;World Health Organization, 2014). Mental disorders are an important risk factor for suicidal behaviour (Bostwick and Pankratz, 2000;Nordentoft et al, 2011;Palmer et al, 2005): of the individuals who committed suicide, 91% had a mental disorder, most commonly a depressive disorder, substance abuse or schizophrenia (Cavanagh et al, 2003;ten Have et al, 2009;Ten Have et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta analysis, Palmer et al (2005) have estimated that 4.9% of patients commit suicide during their lifetimes, usually around the time of onset of the illness. Suicidal risk increases with age (Bille-Brahe, 1993).…”
Section: Introductionmentioning
confidence: 99%